Atlas of Karst Collapses - Lei, Mingtang; Zhou, Wanfang; Jiang, Xiaozhen; Dai, Jianling; Yan, Meng. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book comprehensively documents the various types of karst collapse and related conceptual site models, before discussing these collapses in terms of their impacts on engineering and the environment. Featuring over 200 real-world photos to illustrate the variety of karst collapses and their consequences, the book also provides specific methods and techniques to prevent, investigate, monitor and remediate these collapses. Decades of experience with these collapses make it clear that addressing the related hazards requires a multi-disciplinary approach that integrates geomorphology, engineering geology, hydrology, hydrogeology, biology, geophysics, geochemistry, and risk assessment.
Chapter 1. Karst collapses and their formations -- Chapter 2. Stormwater runoff modifications and karst collapses -- Chapter 3. Water impoundments and karst collapses -- Chapter 4. Groundwater level changes and karst collapses. Chapter 5. Construction and karst collapses -- Chapter 6. Extreme weather conditions and karst collapses -- Chapter 7. Karst collapse investigations -- Chapter 8. Karst collapse monitoring. .
Keywords: Physical geography; Natural disasters; Earth sciences; Geotechnical engineering; Earth System Sciences; Physical Geography; Natural Hazards; Earth Sciences; Geotechnical Engineering and Applied Earth Sciences